The way to a beautiful world - Norbury, James (William Morrow, 2025)
"It's hard to imagine there's light when we are so deep in the darkness. But it's there, so let's keep walking." Sometimes, to find The Most Beautiful Place in the World, we must traverse foreboding terrain. As beloved friends Big Panda and Tiny Dragon journey to find the lost land, there are moments when the dense forests, hazardous mountains, derelict ruins, and dark caves, and the feelings they bring, threaten to overwhelm them. But, together, they find the will to keep on walking. Each environment, so menacing at first, slowly yields glimmers of life, light, and beauty. In an exploration of life-affirming friendship, struggle, and hope, Big Panda and Tiny Dragon learn the immense power of looking for beauty in the most unlikely places."--